2019
DOI: 10.1016/j.earlhumdev.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral problems are associated with cognitive and language scores in toddlers born extremely preterm

Abstract: Objective: To evaluate the relationship of parent-reported child behaviors on the Child Behavior Checklist (CBCL) to cognition, language, and motor skills on the Bayley Scales of Infant and Toddler Development – III (Bayley-III) in toddlers born extremely preterm. Study Design: Toddlers born extremely preterm (gestational ages 22 0/7 to 26 6/7 weeks) were tested at 22 – 26 months corrected age with Bayley-III while parents completed the CBCL. Socio-demographic variables and medical history were recorded. Lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 22 publications
(22 reference statements)
3
11
1
3
Order By: Relevance
“…In our sample, the response rate was 54.2% which is at the lower end reported in other very preterm cohorts in early childhood which range from about 50 to 90% [6,7,12,38,39,40]. Follow-up rates tend to be higher for studies from neonatal networks when compared to population-based studies and those that have regular contact with families after discharge.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In our sample, the response rate was 54.2% which is at the lower end reported in other very preterm cohorts in early childhood which range from about 50 to 90% [6,7,12,38,39,40]. Follow-up rates tend to be higher for studies from neonatal networks when compared to population-based studies and those that have regular contact with families after discharge.…”
Section: Discussioncontrasting
confidence: 55%
“…As in our study, fewer and less consistent associations have been observed between follow-up and perinatal variables which are the strongest predictors of poor outcome for VPT children [44], as we saw in this study; many of the studies cited above report similar neonatal characteristics and morbidities for responders and nonresponders. Higher birthweight has been related to lower follow-up rates in some neonatal network studies which Table 2 Maternal, pregnancy and perinatal characteristics associated with loss to follow-up and the presence or absence of neurodevelopmental impairment at 2 years of corrected age (N = 1737) (Continued) may reflect a closer connection between families and the NICU for higher risk low-birthweight infants [38,39]. In contrast, in some studies, families with more impaired children were less likely to attend clinical assessments or responded by postal questionnaires only versus full participation.…”
Section: Discussionmentioning
confidence: 99%
“…These areas have been linked to natural speech production, particularly synchronous speech (Alexandrou, Saarinen, Kujala, & Salmelin, 2016;Jasmin et al, 2016). VPT children have been highlighted to have language difficulties (Peña, Pittaluga, & Mehler, 2010;Vohr, 2014), which extend to social communication difficulties (Lowe et al, 2019); thus, slower maturation of this brain area may underlie those commonly reported weaknesses in VPT cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Slower maturation of these regions could affect the VPT child's processing of complex visual stimuli, impacting both learning and social behaviour. VPT children have been highlighted to have language difficulties(Peña, Pittaluga, & Mehler, 2010;Vohr, 2014), which extend to social communication difficulties(Lowe et al, 2019); thus, slower maturation of this brain area may underlie those commonly reported weaknesses in VPT cohorts. These areas have been linked to natural speech production, particularly synchronous speech(Alexandrou, Saarinen, Kujala, & Salmelin, 2016;Jasmin et al, 2016).…”
mentioning
confidence: 99%
“…Preterm labor has also been shown to affect negatively language skills of children in toodlerhood (Lowe et al, 2019;Marchman, Adams, Loi, Fernald and Feldman, 2016;Brosch-Fohraheim, Fuiko, Marschik & Resch, 2019). In the studies conducted during the toddlerhood, it was found that humanity affects language development in favor of girls (Gudmundsson, 2015;Stangeland, Lundetrae & Reikeras, 2018).…”
Section: Factors Affecting Language Development In Toddlerhoodmentioning
confidence: 99%